Aspects of tourism : codes of ethics in tourism - Fennell, David A (S.l. : s.n, 2015)
Provides a look at the theory and practice of codes of ethics in tourism. This book includes an overview of what has been done to date in tourism studies in the area of code development and implementation. It also furnishes the study of tourism codes of ethics with a theoretical foundation.